MEKANISME IMUNODEPRESI PASCASTROKE - Al Rasyid* (Neurona Majalah Kedokteran Neuro Sains, 2019)
REFERS TO A CONDITION WHEN IMMUNE SYSTEM HAS REDUCED CAPACITY TO FULFILL ITS FUNCTIONS THEREFORE LEADING TO INFECTION INFECTIONS DEVELOP FREQUENTLY AFTER STROKE AND HAVE BEEN ASSOCIATED WITH POOR CLINICAL AND FUNCTIONAL OUTCOME SEVERAL STUDIES SHOW ISCHEMIC STROKE LEADS TO IMPAIRMENT OF IMMUNE RESPONSES WHICH INCREASES SUSCEPTIBILITY OF AN INFECTION